PtdIns4P-mediated electrostatic forces influence S-acylation of peripheral proteins at the Golgi complex - Chumpen Ramirez, Sabrina Vanesa (2020)
Protein S-acylation is a reversible post-translational modification involving the addition of fatty acids to cysteines and is catalyzed by transmembrane protein acyltransferases (PATs) mainly expressed at the Golgi complex. In case of soluble proteins, S-acylation confers stable membrane attachment. Myristoylation or farnesylation of many soluble proteins constitutes the initial transient membrane adsorption step prior to S-acylation. However, some S-acylated soluble proteins, such as the neuronal growth-associated protein Growth-associated protein-43 (GAP-43), lack the hydrophobic modifications required for this initial membrane interaction. The signals for GAP-43 S-acylation are confined to the first 13 amino acids, including the S-acylatable cysteines 3 and 4 embedded in a hydrophobic region, followed by a cluster of basic amino acids. We found that mutation of critical basic amino acids drastically reduced membrane interaction and hence S-acylation of GAP-43. Interestingly, acute depletion of phosphatidylinositol 4-phosphate (PtdIns4P) at the Golgi complex reduced GAP-43 membrane binding, highlighting a new, pivotal role for this anionic lipid and supporting the idea that basic amino acid residues are involved in the electrostatic interactions between GAP-43 and membranes of the Golgi complex where they are S-acylated.